Model Group Investigation Berbantuan Media Diorama Peristiwa Untuk Meningkatkan Hasil Belajar Siswa - Siti Wahdatul Umah; Suad Suad; Mila Roysa (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
This research aims to improve students' cognitive and psychomotor domains using the group investigation learning model assisted by the diorama event of seventh-themed fifth-grade elementary school two the Panjunan academic years 2019/2020. The research carried out is class action research (Classroom Action Research). Classroom Action Research in 2 Cycles with two meetings for each cycle. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. This action was carried out in the fifth class of elementary school two Panjunan with 29 students. The independent variable was the investigation group model, and the dependent variable was the learning outcome. The research instrument was an observation, interviews, and documentation—the data analysis techniques. The results and student learning in the cognitive domain, in the pre-cycle of the Social Studies moment showed 48% to 45% in the cycle (I) one, soaring in the cycle (II) two with 89.7%. In the cognitive realm, the results and student learning in the Indonesian language pre-cycle showed 83% to 52% in cycle (I) one, soaring in the cycle (II) two with a result of 93.1%. The results of student learning in the psychomotor domain, from the cycle (I) one with a value of 76% good category (B) jumped by 81% good category (B) in the cycle (II) two. These results indicated that the investigation group had better.Keywords: Cognitive and Psychomotor Ability, Group Investigation, Diorama of Events====================================================================================================Penelitian ini bertujuan untuk mendeskripsikan peningkatan hasil belajar menggunakan model pembelajaran group investigation berbantuan media diorama peristiwa tema 7 kelas V SD 2 Panjunan. Penelitian tindakan kelas ini dilakukan di kelas V SD 2 Panjunan dengan subjek penelitian 29 siswa berlangsung selama dua siklus, setiap siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Variabel bebasnya adalah model group investigation dan variabel terikat adalah hasil belajar. Instrumen penelitian ini adalah observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis data kualitatif dan kuantitatif. Hasil belajar siswa ranah pengetahuan, di prasiklus muatan IPS memperoleh 48% menjadi 45% di siklus I, meningkat di siklus II sebesar 89,7%. Hasil belajar siswa ranah pengetahuan, di prasiklus muatan Bahasa Indonesia memperoleh 83% menjadi 52% di siklus I, meningkat di siklus II sebesar 93,1%. Hasil belajar siswa ranah keterampilan, dari siklus I sebesar 76% (baik) meningkat sebesar 81% (baik) dalam siklus II.Kata kunci: Hasil Belajar, Group Investigation, Diorama Peristiwa